2009
DOI: 10.1021/jf8030524
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Optimizing an Immunoaffinity Cleanup Technique for Determination of Quinolones from Chicken Muscle

Abstract: An immunoaffinity chromatographic method was developed using an antibody mediated immunosorbent to selectively extract and purify 10 quinolones (marbofloxacin, norfloxacin, ciprofloxacin, lomefloxacin, danofloxacin, enrofloxacin, difloxacin, sarafloxacin, oxolinic acid, and flumequine) in chicken muscle followed by HPLC. The operating conditions of the immunoaffinity chromatography (IAC) column were optimized, and the IAC has been successfully used for the isolation and purification of 10 quinolones from chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…In the field of food safety, IAC has been widely used in sample pretreatment for residue analysis of mycotoxin, veterinary drugs, pesticides, phycotoxins, process and environmental contaminants and vitamins [5][6][7][8]. Sepharose is commonly used as support matrix for chromatography because of its porosity, chemical and mechanical stability.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of food safety, IAC has been widely used in sample pretreatment for residue analysis of mycotoxin, veterinary drugs, pesticides, phycotoxins, process and environmental contaminants and vitamins [5][6][7][8]. Sepharose is commonly used as support matrix for chromatography because of its porosity, chemical and mechanical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Although a range of monoclonal antibodies are commercially available from a number of suppliers, preparing columns does limit applicability to those with the skills and experience to couple the antibody to a gel and be able to prepare a robust column. Nevertheless, many recent publications still involve the use of IACs prepared in the authors own laboratory [32][33][34], and although full experimental details of preparation are given, most analytical chemists will err towards purchasing commercial columns if available. A comparison of commercial and in-house columns [35] clearly showed that even some commercial columns can fail to adequately entrap and then to elute the analyte.…”
Section: Introductionmentioning
confidence: 99%
“…Using an immunoaffinity column the group successfully developed a method to isolate 13 quinolones and six SAs in swine and chicken muscle. Zhao and Li et al used the same method to isolate 10 quinolones in chicken muscle but used HPLC-FL for analysis [123]. The authors note the possibility of greater selectivity when using such IA columns, compared with the smaller range of interaction mechanisms available for exploitation with more conventional SPE formats.…”
Section: Quinolonesmentioning
confidence: 99%